(untitled) (Teaching and Learning Inquiry, 2024)
Post-truth strategies are characterized by the manipulation of facts and personal assertions of the truth for political gain. By seeding polarization, skepticism, and mistrust, post-truth presents challenges to teaching and learning within academic settings. In this paper, we explore how post-truth is articulated in higher education literature using a critical pedagogical lens. We suggest that pedagogical scholarship needs to expand its scope beyond a focus on the media antics of individual politicians in order to interrogate the reliance on dominant framings that simply define “post-truth” as circumstances where personal beliefs take precedence over established facts. We argue that the current framing of post-truth shapes the educational response to this issue, which focuses on helping students discern correct from incorrect information, as opposed to teaching students how power and knowledge are intertwined in post-truth and ways to understand and address the subsequent and potentially harmful power relations. Since post-truth strategies are enacted to restrict thoughtful reflection on dominant relations of power, we propose a critical pedagogical framework to problematize the notion of objective truth, account for the politics of exclusion, examine power relations, and contest post-truth strategies. Read the corresponding ISSOTL blog post here.